MENGUAK REKLAMASI TELUK BENOA DALAM ANALISIS WACANA KRITIS TEUN A.VAN DIJK - Anak Agung Ayu Dian Andriyani; I Komang Sulatra Sulatra; I Wayan Juniarta Juniarta (SASTRANESIA: Jurnal Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2020)
This qualitative research utilizes the Teun A. van Dijk’s critical discourse approach and aims to describe 3 main dimension of text, they are text in macro structure, super structure, and micro structure of social cognition as well as social context in daily newspaper Bali Post with headlines entitled ‘Reklamasi Teluk Benoa Mematikan Ekonomi Rakyat’ published on 16th February 2016. The technique used in collecting data is Sudaryanto’s observation method and taking note. Furthermore, this research uses van Dijk’s approach in analyzing data. The findings show the result as follows: 1) text can describe the context into supra structure level, which means macro structure and micro structure are formed by the facts occurred in society. It is reflected with the lexical choices using metaphorical expression that is described persuasively by hyperbolical language. 2) From social cognitive point of view, reporters acknowledged what is happening so well since they are trying to persuade the readers to refuse the government policies related with the reclamation of Benoa Bay, yet still following the journalism code of ethics; 3) Based on social context analysis, there are pros and contras from society who support and refuse the government policies, and there is industrialist involvement in taking action onto the reclamation.